THE EFFECTIVENESS OF ESTIMATED FETAL WEIGHT WITH NISWANDER METHOD FOR WEIGHT BABY BORN IN MATERNITY UNIT OF MOTHER AND BABY HOSPITAL IN RSB MUTIARA BUNDA SALATIGA - Sumantri . (STIKES DUTAGAMA KLATEN, 2013)
Background : Estimated Fetal Weight intra-uterine has important significance in the management of labor. There are various ways to determine the estimated namely : palpation, ultrasound and fundal height measurements . From the results of a preliminary survey in mother and baby hospital in RSB Mutiara Bunda Salatiga the average of baby born every year around 960 birth. Objective : to determine the effectiveness of the estimated fetal weight with Niswander method compared to the method of Johnson Toshack weight newborns. Methods : The study was observational analytical case-control design and a sample of 91 respondents . Sampling techniques using simple random sampling . Analyses using Chi Square and Odd Ratio.Results: The results showed that the accurate of Niswander method was 48.35 %, while Johnson Toshack was 65.93 % with the odds ratio 0.296 and p value 0.009 with CI 95 % of 0.119 to 0.739. Conclusion : the calculation of estimated fetal weight by the method of Johnson's was more effective than Niswander with the accuracy of 65.93 % , while 48.35 % of Niswander , p value was 0.009 , Odd Ratio of 0.296 and CI 95% was 0.119 - 0.739 . It shows that the method of Niswander is less effective in assessing weight newborns compared to Johnson Toshack.